Serangan Perenosclerospora spp Pada Tanaman Jagung Di Desa Rumahtiga, Kecamatan Teluk Ambon Baguala Kota Ambon - Angel E Matruti; A. Marthin Kalay; Costanza Uruilal (Faculty of Agriculture, Pattimura University, 2013)
Peronosclerospora spp. is one of the fungal pathogen that causes downy mildew on corn, and can cause yield losses up to 100%. Field research has been done to determine the development of Perenosclerospora spp. attack and contributing factors on corn at corn plantation in Rumahtiga village. The experiment was conducted by using survey method at local farmer’s plantation where they cultivated corn in Taeno Hamlet, Talaga Pange, Air Ali, and Wailela areas. The results showed that downy mildew development in corn reached 8.92% which is belong to low diseases intensity. Cultivation techniques including the use of hybrid varieties C1, appropriate fertilization, crop rotation and weed control, as well as good sanitation were key factors of low scale infestation of Peronosclerospora spp.